Chemical Composition of Essential Oils from Needles of Pinus pinaster from Italy and Tunisia - Marzouki, H.; Falconieri, D.; Marongiu, B.; Piras, A.; Porcedda, S. (Asian Journal of Chemistry, 2015)
The chemical composition of the essential oil obtained from the needles of Pinus pinaster by hydrodistillation was analyzed by gas chromatography-mass spectrometry. Fifty components were detected, of which 41 were identified for a total percentage of about 98 %. The main components of the essential oil of needles from Tunisia were abietadiene (25.4 %), 13-epi-manoyl oxide (16.6 %), abietatriene (10.2 %), b-caryophyllene (11.1 %), 13(16), 14-labdien-8-ol (5.9 %) and a-pinene (5.3 %) whereas the oil from Italy was predominantly composed of limonene (36.7 %), abienol (13.4 %), manoyl oxide (6.5 %) and b-caryophyllene (5.8 %).